The goddess incarnate: A discourse on the body within one community of contemporary North American goddess worshippers - DuFresne, Lucie Marie-Mai (University of Ottawa (Canada), 2004)
For the past 30 years, a feminist spirituality movement has been developing in North America. Variously called Goddess Worship, Goddess spirituality, or Women's spirituality, it derives in part from Neo-paganism and Contemporary Witchcraft, on the one side, and feminist liberation theology on the other. Continuing the questioning begun by Simone de Beauvoir on female self and other, on gender and its construction, and on the merits of a morality of indeterminacy, this ethnography of a community of like minded women who participate together in devotional circles to the Goddess in and around Ottawa, Ontario, Canada focuses on the ritual, textual and iconological means by which these women come to an embodied relationship with the divine apprehended as female. By deconstructing the actions, the words, and the images of the human body, as the locus of contact with the divine, and the divine body as the central cosmological metaphor of this spirituality produced and used by these women, the ritual and ethical discourses on identity, power and agency built around them are made evident. Compared and contrasted, they then are studied as charters for the construction of the self and community.
Keywords: Women's Studies.